Kepemimpinan Transformasional Perguruan Tinggi dalam Meningkatkan Mutu Lulusan Melalui Penguatan Tata Kelola Berbasis Ekonomi Islam di Universitas Kepanjen Malang - Bambang Suryanto; Tulus Suryanto; Pertiwi Utami (MAMEN: Jurnal Manajemen, 2026)
The quality of graduates is one of the key indicators of a university’s success in delivering education. Efforts to improve graduate quality cannot be separated from the role of effective leadership and well-implemented governance. Transformational leadership and Islamic economic-based governance are considered important approaches that can enhance higher education management and produce competent graduates. This study aims to examine the implementation of transformational leadership at Kepanjen University Malang, analyze the application of Islamic economic-based governance in improving graduate quality, and explore the outcomes of transformational leadership implementation through strengthening Islamic economic-based governance at the university.This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. The informants consisted of university leaders, lecturers, administrative staff, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings show that transformational leadership at Kepanjen University Malang is implemented through the development of vision, motivation, and competency improvement of the academic community. Islamic economic-based governance is applied by integrating values such as trustworthiness (amanah), honesty, justice, transparency, and responsibility in institutional management and learning processes. The combination of these approaches contributes positively to improving graduates’ academic competence and Islamic character. This study employed a qualitative approach with a case study research design. Data were collected through interviews, observations, and documentation. The informants of this research consisted of university leaders, lecturers, administrative staff, and students. Data analysis was carried out through data reduction, data display, and conclusion drawing. Meanwhile, data validity was tested through source triangulation and method triangulation. The results of the study indicate that: (1) the implementation of transformational leadership at Kepanjen University Malang is carried out through providing vision, motivation, and the development of academic community competencies in improving the quality of education; (2) the implementation of Islamic economic-based governance is conducted by integrating Islamic values such as trustworthiness (amanah), honesty, justice, transparency, and responsibility in institutional management and learning processes; and (3) the implementation of transformational leadership supported by Islamic economic-based governance has a positive impact on improving the quality of graduates, both in terms of academic competence and character building based on Islamic values